Prevailing Calf Mortality and its Pattern in Indigenous Cattle in Operational Area of Dairy Vigyan Kendra, Vejalpur, Gujarat - Jadav, Sanjay J.; Patel, Yogesh G.; Panigrahy, Shaktiranjan (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The objective of this study was to assess the prevailing indigenous calf mortality & its pattern in the operational area of Dairy Vigyan Kendra (DVK), Vejalpur, Gujarat, India. Using the simple random sampling method, 300 indigenous cattle owners from 6 villages each from 10 talukas were selected for the study from August to December 2021. The data were collected based on the pre-tested structured interview schedule. Overall indigenous calf mortality was observed 27.90 % in the study area. There was a higher mortality rate in male calves (53.43%) than in female indigenous calves (11.97%) due to limited attention towards the male calf. The mortality rate was recorded higher during the first three months of age (76.42%) and during the summer (50.00%). The major reason of calf mortality was diarrhoea or dysentery. Most indigenous cattle owners had not adopted the recommended calf management practices. Farmers urgently need extension services on scientific calf rearing practices such as cutting navel cord with sterilized object, providing colostrum and milk as per body weight, on-time colostrum feeding, provision of milk replacer, calf starter, salt, mineral mixture, deworming, and HS & FMD vaccination.